Quantification of Functional and Inactivated α2-Macroglobulin in Sepsis - Abbink, J J; Nuijens, J H; Eerenberg, A J M; Huijbregts, C C M; Strack van Schijndel, R J M; Thijs, L G; Hack, C E (Thrombosis and Haemostasis, 1991)
Alpha2-macroglobulin (α2M) in vitro inhibits numerous proteinases that are generated during inflarnmatory reactions and therefore, probably plays an important role in diseases such as sepsis. To monitor the state of α2M in sepsis, we developed novel assays for functional and inactive α2M. Functional α2M in palsama trypsin. Inactive α2M (iα2M) was assessed with a monoclonal antibody, mcAb M1, that specifically reacts with a neodeterminant exposed on iα2M. This mcAb in combination with chromogenic substrates was used to detect α2M-proteinase complexes.Functional α2M was reduced in plasma from 48 patients with clinical sepsis compared to healthy controls (p <0.0001). Levels of functional α2M on admission and the lowest levels encountered in 23 patients with shock were lower than in 25 normotensive patienis (p = 0.023 and p = 0.009, respectively). Increased levels of iα2M (>30 nM) at least on one occasion were found in only 4 of the 48 patients, being not different in hypotensive compared With normotensive patients, and not in patients who died compared with those who survived. Levels of functional α2M correlated significantly with levels of factor XII and prekallikrein suggesting that decreases in α2M at least in part were due to contact activation. Indeed, in two patients with increased iα2M, complexes between α2M and kallikrein were demonstrated in addition to plasmin- and thrombin-α2M complexes.